Candida albicans-Staphylococcus aureus Polymicrobial Peritonitis Modulates Host Innate Immunity - Peters, Brian M. (American Society for Microbiology, 2013)
Despite advances in medical device fabrication and antimicrobial treatment therapies, fungal-bacterial polymicrobial peritonitis remains a serious complication for surgery patients, those on peritoneal dialysis, and the critically ill. Using a murine model of peritonitis, we have demonstrated that monomicrobial infection with Candida albicans or Staphylococcus aureus is nonlethal. However, coinfection with these same doses leads to a 40% mortality rate and increased microbial burden in the spleen and kidney by day 1 postinfection. Using a multiplex enzyme-linked immunosorbent assay, we have also identified a unique subset of innate proinflammatory cytokines (interleukin-6, granulocyte colony-stimulating factor, keratinocyte chemoattractant, monocyte chemoattractant protein-1, and macrophage inflammatory protein-1α) that are significantly increased during polymicrobial versus monomicrobial peritonitis, leading to increased inflammatory infiltrate into the peritoneum and target organs. Treatment of coinfected mice with the cyclooxygenase (COX) inhibitor indomethacin reduces the infectious burden, proinflammatory cytokine production, and inflammatory infiltrate while simultaneously preventing any mortality. Further experiments demonstrated that the immunomodulatory eicosanoid prostaglandin E(2) (PGE(2)) is synergistically increased during coinfection compared to monomicrobial infection; indomethacin treatment also decreased elevated PGE(2) levels. Furthermore, addition of exogenous PGE(2) into the peritoneal cavity during infection overrode the protection provided by indomethacin and restored the increased mortality and microbial burden. Importantly, these studies highlight the ability of fungal-bacterial coinfection to modulate innate inflammatory events with devastating consequences to the host.